2005
DOI: 10.1002/pat.630
|View full text |Cite
|
Sign up to set email alerts
|

The preparation and characterization of silver‐loading cellulose acetate hollow fiber membrane for water treatment

Abstract: Silver‐loading asymmetric cellulose acetate (CA) hollow fiber membrane was spun via the dry jet‐wet spinning technique. The spinning solution was prepared by dissolving AgNO3 and CA in N,N‐dimethylformamide (DMF). The silver ions were reduced in the spinning dope into silver nano‐particles. The morphology of the resulting hollow fibers was examined using a scanning electron microscope and the silver content in the fiber was measured using an inductively coupled plasma atomic emission spectrometer. The antibact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
173
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(177 citation statements)
references
References 18 publications
2
173
1
1
Order By: Relevance
“…Biofouling can be avoided using the bactericidal properties of silver nanoparticles, and indeed, silver is a typical example of a bactericide that is used for fouling mitigation in polymeric membranes. Escherichia coli and Staphylococcus aureus have typically been used as model organisms to evaluate the antimicrobial properties of AgNpimpregnated CA membranes [32]. However, in this study, we evaluated the antimicrobial activity of AgNps against M. smegmatis.…”
Section: Antimycobacterial Membrane Studiesmentioning
confidence: 99%
“…Biofouling can be avoided using the bactericidal properties of silver nanoparticles, and indeed, silver is a typical example of a bactericide that is used for fouling mitigation in polymeric membranes. Escherichia coli and Staphylococcus aureus have typically been used as model organisms to evaluate the antimicrobial properties of AgNpimpregnated CA membranes [32]. However, in this study, we evaluated the antimicrobial activity of AgNps against M. smegmatis.…”
Section: Antimycobacterial Membrane Studiesmentioning
confidence: 99%
“…Although, there are number of researchers which reported that P. amarus and T. cordifolia have shown antimicrobial activity against pathogenic microbial strains [16][17][18][19][20]. Whereas, the antimicrobial properties of silver compounds and silver ions had been historically recognized and applied in the wide range of applications [21]. Due to the growing need to develop environmentally benign technologies in material synthesis, biosynthesis of nanoparticles has received considerable attention [22].…”
Section: Antimicrobial Efficacymentioning
confidence: 99%
“…Rapid silver depletion could be addressed by future research focusing on better nAg fixation techniques that concentrate the silver near the surface of the membrane (where it is most effective) and encapsulate the silver to slow the release rate. Because eventual silver depletion may be unavoidable, the effectiveness of nAg regeneration by reductive deposition of silver salts should be further explored (Chou et al, 2005;Deng et al, 2008). While nAgimpregnated membranes would not guarantee protection against silver-resistant bacteria strains, they may ensure antimicrobial activity against a wide variety of bacteria and viruses and provide long-term protection against biofouling and viral penetration of water filtration membranes.…”
Section: Conclusion Engineering Significance and Future Research Nmentioning
confidence: 99%
“…Nanosilver has been incorporated into cellulose acetate (Chou et al, 2005), polyimide (Deng et al, 2008), polyamide (Damm et al, 2007), and poly(2-ethyl-2-oxazoline (Kang et al, 2006) membranes on the lab scale. However, the long-term effectiveness of the incorporated nAg in preventing biofouling during continuous filtration has not been addressed.…”
Section: Silver Nanoparticles In Water Treatment Membranesmentioning
confidence: 99%